The transforming family: Heterologous fertilization and the new expressions of family relationships in Italian jurisprudence and European Court of Human Rights rulings. (December 2019) - Montanari Vergallo, Gianluca
The rise of Medically Assisted Procreation has led to the issue of how to determine who is entitled to parental status and custody rights. In this article, the author comments upon the rationale and legal principles that Italian Courts have applied in order to solve those problems, given the absence of a targeted piece of legislation. The principle of the child's best interests, the 'public order' clause and various rulings from the European Court of Human Rights constitute the foundations on which legal trends have developed, allowing same-sex couples to become parents through 'stepchild adoption' or the legal registration of children born through heterologous fertilization practices abroad. Italy has therefore repositioned itself a step closer to the middle ground with respect to the overall European scenario: Italy's law now acknowledges motherhood for intended mothers, although it continues to stop short of recognizing same-sex marriage.